Pengaruh Layanan Informasi Media Padlet Terhadap Pemahaman Covid-19 Pada Siswa Kelas X SMAN 1 Batu Layar - Maris Ramdhani Saputro; Ni Ketut Alit Suarti; Jessica Festy Maharani (Jurnal Eduforia: Jurnal Penelitian dan Pengembangan Pendidikan, 2026)
This study aims to determine the effect of information services delivered via the Padlet platform on students' understanding of COVID-19. The study was motivated by students' limited understanding of health information and the suboptimal use of digital media in guidance and counseling services. A quantitative approach was employed using a pre-experimental, one-group pre-test/post-test design. The sample consisted of 31 Grade X students from SMAN 1 Batu Layar, selected using a total sampling technique. Data were collected via a COVID-19 understanding questionnaire and analyzed using a t-test. The results revealed a calculated t-value of 9.405, which exceeded the t-table value of 2.042 at a significance level of 0.05. This indicates that Padlet-based information services significantly improved students' understanding of COVID-19. Thus, digital media offers an innovative alternative for enhancing the effectiveness of school guidance and counseling services.